A comparative prospective open label randomized controlled 8 week study in patients of depression treated with vilazodone and sertraline - Arya, Nirmal; Nischal, Anuradha; Nischal, Anil; Agarwal, Manu (International Journal of Advances in Medicine, 2020)
Background: Depression is a mood disorder treated with various antidepressant such as SSRIs due to lesser toxicity and improved safety profile. Methods: This was an eight week randomised active controlled parallel group study. 54 patients were allocated in two group. Group A received vilazodone while group B received sertraline. Assessment done at baseline, 2, 4 and 8 weeks on the basis of clinical efficacy, sexual dysfunction, side effects and weight gain using Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), Arizona Sexual Experience Scale (ASEX) and UKU Side Effect Rating Scale. Results: HAM-D score of group A was 18.78±1.78 and 7.67±1.66 while in group B was 19.04±2.12 and 8.15±1.77 at baseline and 8 weeks respectively. HAM-A score of group A was 15.44±1.50 and 6.63±1.39 while in group B was 15.26±1.83 and 7.07±1.14 at baseline and 8 weeks. ASEX total score of group A was 15.63±1.28 and 14.63±1.33 while group B was 15.52±1.37 and 16.41±1.12 at baseline and 8 weeks. ASEX desire score of group A was 9.63±0.93 and 8.67±0.88 while of group B was 9.59±0.93 and 10.07±0.92 at baseline and 8 weeks. UKU side effect rating at 2 and 8 weeks of group A was 0.22±0.42, 1.04±0.76 while in group B was 0.37±0.49, 1.89±0.85. Conclusions: Vilazodone and Sertraline are equally efficacious in treatment of depression and associated anxiety. When side effect profile were compared Vilazodone is found superior to Sertraline